Kan kvinnor vara renskötare? - Udén, Maria (Luleå tekniska universitet, Arbetsvetenskap, 2007)
Can women be reindeer herders? A woman who is a reindeer herder asked for assistance from LTU, to shed light over that topic, as her Sámi village was starting a gender equality project in 2001. This report develops the material gathered during the two years of research and cooperation that developed as result of the request. The material includes fifteen interviews with reindeer herders and reindeer owners, and observation and participatory observation. The topics brought up include the Swedish legislation, "Rennäringslagen"- the reindeer herding law, and an investigation of possible benefits in terms of relevant knowledge development gained by applying two particular feminist concepts to the analysis: "doing gender" and "the nomadic subkect". References include Andrea Amft, Jorun Eikjokk and others who have published on the topic of gender and gender equality in reindeer herding and Sámi communities in Scandinavia. The snow mobile has a central position in the report, as it has in contemporary popular local explanations to "why women cannot be reindeer herders". Kan kvinnor vara renskötare? Den frågan ville en kvinna som är just renskötare, att Luleå tekniska universitet skulle hjälpa till att belysa. Den här uppsatsen är en bearbetning av det forskningsmaterial som samlades in som resultat av förfrågan. Där ingår ett femtontal intervjuer med renskötare och renägare, samt observation och deltagande observation kopplat till samebyns jämställdhetsprojekt under dryga två års tid. Uppsatsen tar upp rennäringslagen, och möjligheter att belysa situationen med hjälp av två feministiska teoretiska ansatser (med begreppen Doing gender respektive nomaditet i fokus). Referenser finns till Andrea Amft, Jorun Eikjokk med flera forskare som publicerat kring frågan om genus/jämställdhet och renskötsel i Norden. Snöskotern har en central roll i analysen, eftersom den har en central roll i de folkliga förklaringarna till bristande jämställdhet i renskötseln. Bevisligen finns det kvinnliga renskötare, inklusive äldre kvinnor ...